Health-promoting effects of Clostridium butyricum GKB7 on the gastrointestinal tract in murine models - You-Shan Tsai; Chia-Chi Chen; Li-Ya Lee; Shih-Wei Lin; Yen-Lien Chen; Chin-Chu Chen (Biochemistry and Biophysics Reports, 2025)
Clostridium butyricum is an anaerobic bacterium known for its ability to produce butyrate and modulate gut microbiota. This study aimed to evaluate the protective and regulatory effects of a novel strain, Clostridium butyricum GKB7, isolated from a healthy Taiwanese individual, on gastrointestinal tract. Three rodent disease models were established: picrylsulfonic acid-induced colitis in rats, loperamide-induced constipation in rats, and aspirin-induced gastric ulcers in mice. Strain GKB7 was administered orally at doses equivalent to human intake with 100 mg/60kg/day. It was found that strain GKB7 significantly normalized colon length and weight, reduced intestinal injury, and partially protected the enterochromaffin cell in colitis model. Besides, strain GKB7 improved stool water content over time and significantly enhanced gastrointestinal motility in constipation model. Furthermore, strain GKB7 mitigated gastric ulcer severity and tissue damage, achieving a 25.2 % curative ratio in gastric ulcer model, with observed reductions in ulcer depth, area, and inflammation. C. butyricum GKB7 exhibits probiotic potential by improving colonic integrity, promoting bowel movement, and protecting against gastric injury. These results support its potential as a supplement for gastrointestinal disorders including inflammatory bowel disease, constipation, or peptic ulcers.